Implementasi Landasan Psikologi Pendidikan Guru di SDK Ende 3 - Ansel, Maria Finsensia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research is based on teachers' problems in implementing the psychological foundation of teacher education at SDK Ende 3 Flores, East Nusa Tenggara. Class teachers face many problems when they have to apply the psychological foundations of education in the classroom. Researchers conducted research regarding the analysis of the implementation of the psychological foundations of education that have been applied by teachers at SDK Ende 3. The aim of this research is to examine (1) how SDK Ende 3 teachers implement the psychological foundations of education (2) examine the implementation of the psychological foundations of education in elementary schools based on curriculum. This research uses a descriptive qualitative approach. The research was conducted at SDK Ende 3. This research analyzes teachers who have implemented and implemented the psychological foundations of education. Data collection techniques include observation, interviews, questionnaires and documentation. Data analysis techniques include data reduction, data presentation and data verification. The results of the research show that teachers at SDK Ende 3 have implemented the psychological foundations of education in daily learning.